Substantiating the expediency of using hydrogen fuel cells in electricity generation - Boichenko, Sergii; Danilin, Oleksandr; Shkilniuk, Iryna; Yakovlieva, Anna; Khotian, Artem; Pavlovskyi, Maksym; Lysak, Roksolana; Shamanskyi, Sergii; Kryuchkov, Anatoliy; Tarasiuk, Oksana (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the process of using a hydrogen fuel cell to generate and accumulate electricity. The study highlights the feasibility of using a hydrogen fuel cell to provide electrical load. The potential of using hydrogen as an alternative energy source was evaluated. SWOT analysis was used as a research method, based on the results of which recommendations were developed. The proposed measures could be taken to increase the use of hydrogen energy as an alternative to traditional energy sources. The use of hydrogen technologies in an administrative building connected to an existing electrical network was analyzed. The economic and environmental aspects of the use of hydrogen fuel cells to meet the demand for electrical load were investigated. Six schemes of energy supply of the building and comparing them to select the optimal solution have been developed. In the study, the assessment tool was the Hybrid Optimization of Multiple Energy Resources (HOMER) software. The considered schemes were evaluated in accordance with a single generalized indicator. As a result, it was determined that the use of a hydrogen fuel cell could increase the efficiency of the traditional system by 85 %. For renewable energy systems, there was an increase in efficiency of 7 % (for the wind generator) and 10 % (for the photocell). The practical use of the results will contribute to the efficiency of the process of electricity production by equalizing the stability of energy supply in hybrid systems. The economic and environmental assessment conducted demonstrates the prospects of using a hydrogen fuel cell. This assessment is designed to strengthen consumer confidence in the use of hydrogen fuel cells and hydrogen in general